(untitled) (Health Renaissance, 2014)
Background: Wooden foreign bodies (WFB) are usually not detectable on radiography. Ultrasound is a useful tool for detection and localization of WFB. Objectives: We evaluated the efficacy of tissue harmonic sonography in detection of WFB and describe the imaging features of WFB on tissue harmonic imaging. Methods: We retrospectively evaluated 28 patients with history of wooden (wood/thorn/bamboo) foreign body prick with tissue harmonic sonography. Results: The WFB was detected on ultrasonography in all 28 patients (100%) which was confirmed on surgery or follow up study. All WFB were echogenic casting strong posterior acoustic shadowing with or without surrounding hypoechoic halo. Conclusion: Tissue harmonic imaging is useful tool for detection and localization of retained WFB. DOI: http://dx.doi.org/10.3126/hren.v11i3.9650 Health Renaissance 2013;11(3):267-269